Gender as a determinant of physical activity levels and mental health of medical students from Poland and Belarus in the context of the COVID-19 pandemic - Baj-Korpak, Joanna; Zaworski, Kamil; Szymczuk, Ewa; Shpakou, Andrei (Frontiers in Public Health, 2023)
Background COVID-19 pandemic has brought about unfavourable changes regarding both physical activity (PA) levels and patterns of behaviour associated with mental health. The study sought to assess PA levels and kinesiophobia in medical students from Poland and Belarus taking account of gender. Methods A total of 779 students (405 students from University of Grodno (UG), Belarus, and 374 students from John Paul II University of Applied Sciences (ABNS) in Biala Podlaska, Poland) took part in the study. Women constituted 74.2% of the study population. A diagnostic survey as well as two research tools, i.e., the International Physical Activity Questionnaire (IPAQ)—short form, and the Tampa Scale for Kinesiophobia (TAMPA) were employed in the study. Results Students from ABNS manifested significantly higher levels of PA. Taking into account gender, male respondents displayed significantly higher levels of MET-min/week (MET—metabolic equivalent of task). As for kinesiophobia, significantly higher levels were demonstrated by students from UG. Its higher levels were also noted among women. Conclusion The findings of the study did not reveal strong correlations between kinesiophobia and PA levels in students from Poland and Belarus in the context of different approaches to the pandemic that both countries adopted. Students from ABNS proved to be more physically active. In turn, participants from UG exhibited significantly higher levels of kinesiophobia. Gender was the factor that significantly differentiated levels of kinesiophobia, with women displaying its higher levels.